Casual analysis: Impact evaluation and causal machine learning with application in R - Huber, Martin (London The MIT Press, 2023)
Reasoning about cause and effect$1 (Bthe consequence of doing one thing versus another$1 (Bis an integral part of our lives as human beings. In an increasingly digital and data-driven economy, the importance of sophisticated causal analysis only deepens. Presenting the most important quantitative methods for evaluating causal effects, this textbook provides graduate students and researchers with a clear and comprehensive introduction to the causal analysis of empirical data. s